2021
DOI: 10.1002/er.6891
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of a new combined energy system includes parabolic dish solar collector, Stirling engine and thermoelectric device

Abstract: Summary According to new findings, the use of clean energy sources such as solar energy to supply energy (both electricity and heat) to human societies is essential. On the other hand, choosing the appropriate technology to convert solar energy into useful energy in the form of individual or combined systems is a fundamental issue. Individual solar energy systems have inherently low performance. However, their use in hybrid energy systems with other energy generation devices is key solution and shows high perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(55 citation statements)
references
References 60 publications
0
55
0
Order By: Relevance
“…According to the results of General Circulation Models (GCM) capable of predicting the climate, the Earth will face an average temperature increase of about 1 to 3.5 • in 2100. 7 Using global data from the last century, it has been shown that if the Earth's temperature rises by one degree, the runoff will increase by 4% on a global scale. 8,9 Therefore, climate change and its impact must be studied to adopt regular policies to understand and control its negative consequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of General Circulation Models (GCM) capable of predicting the climate, the Earth will face an average temperature increase of about 1 to 3.5 • in 2100. 7 Using global data from the last century, it has been shown that if the Earth's temperature rises by one degree, the runoff will increase by 4% on a global scale. 8,9 Therefore, climate change and its impact must be studied to adopt regular policies to understand and control its negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous models have been proposed to study global climate change and its impact on the hydro‐geomorphological characteristics of the watershed. According to the results of General Circulation Models (GCM) capable of predicting the climate, the Earth will face an average temperature increase of about 1 to 3.5° in 2100 7 . Using global data from the last century, it has been shown that if the Earth's temperature rises by one degree, the runoff will increase by 4% on a global scale 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] A formula of the FRP-confined concrete column by considering the optimized AlexNet-ELM-ARFO is presented in. [7] The optimized AlexNet-ELM-ARFO Algorithm is presented here and it is employed for predicting the compressive strength of FRP-confined concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different types of approaches were presented for this purpose. The use of meta-heuristic algorithms, due to their ability for faster and simpler solving of nonlinear models, are exponentially increasing [13][14][15][16]. Some examples of these methods are the dragonfly algorithm [17], deer hunting optimizer [18_ENREF_20], multi-verse optimizer [19_ENREF_18], improved invasive weed optimization algorithm [20_ENREF_19], and chaotic grasshopper optimizer [21].…”
Section: Introductionmentioning
confidence: 99%